2018
DOI: 10.1111/febs.14663
|View full text |Cite
|
Sign up to set email alerts
|

Toward understanding genomic instability, mitochondrial dysfunction and aging

Abstract: The biology of aging is an area of intense research, and many questions remain about how and why cell and organismal functions decline over time. In mammalian cells, genomic instability and mitochondrial dysfunction are thought to be among the primary drivers of cellular aging. This review focuses on the interrelationship between genomic instability and mitochondrial dysfunction in mammalian cells and its relevance to age‐related functional decline at the molecular and cellular level. The importance of oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 184 publications
(231 reference statements)
1
25
0
Order By: Relevance
“…Several neurological disorders originating from deficient DNA repair often involve oxidative stress (1,6,10). DNA repair proteins whose deficiencies are associated with oxidative stress in the brain (3,11) include ataxia-telangiectasia mutated (ATM) kinase, meiotic recombination 11 (MRE11), Nijmegen breakage syndrome 1 (NBS1), aprataxin (APTX), and tyrosyl-DNA phosphodiesterase 1 (TDP1) (1,3). Murine ATM models facilitate clarification of links between genomic instability and impaired redox homeostasis.…”
mentioning
confidence: 99%
“…Several neurological disorders originating from deficient DNA repair often involve oxidative stress (1,6,10). DNA repair proteins whose deficiencies are associated with oxidative stress in the brain (3,11) include ataxia-telangiectasia mutated (ATM) kinase, meiotic recombination 11 (MRE11), Nijmegen breakage syndrome 1 (NBS1), aprataxin (APTX), and tyrosyl-DNA phosphodiesterase 1 (TDP1) (1,3). Murine ATM models facilitate clarification of links between genomic instability and impaired redox homeostasis.…”
mentioning
confidence: 99%
“…Examples of diseases related to mitochondrial repair system; FEN1-flap endonuclease, AMP-adenosine monophosphate, dRP-deoxyribose phosphate lyase, PNKP-polynucleotide kinase 3 -phosphatase, APTX-aprataxin, TDP1-tyrosyl-DNA phosphodiesterase 1, ATM-ataxia telangiectasia mutated, LigIII-ligase III, OMIM database-Online Mendelian Inheritance in Man [192][193][194][195][196]. Recently, mitochondrial disorders are also observed in relation to cancer development, neurodegenerative diseases, aging, and metabolic syndrome [78,197,198]. In the case of cancer, it is believed that mutations in mtDNA that lead to impaired respiration contribute to the propagation of cancerous phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, mitochondrial disorders are also observed in relation to cancer development, neurodegenerative diseases, aging, and metabolic syndrome [ 78 , 197 , 198 ]. In the case of cancer, it is believed that mutations in mtDNA that lead to impaired respiration contribute to the propagation of cancerous phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence indicates that DNA damage and mutation accumulate with age in multiple human and animal tissues, and loss of genome integrity, i.e. nuclear and mitochondrial DNA, is a hallmark of aging across species ( Bua et al, 2006 ; Chow and Herrup, 2015 ; Fakouri et al, 2018 ; Fayet et al, 2002 ; Kalfalah et al, 2015 ; Li et al, 2017 , 2016 ; Lopez-Otin et al, 2013 ; Mattson and Arumugam, 2018 ; Maynard et al, 2015 ; Vaidya et al, 2014 ; Zhang and Vijg, 2018 ; Zhang et al, 2015 ).…”
Section: Genome Instabilitymentioning
confidence: 99%
“…As we discussed in section 4 , damage to DNA can cause a number of unpredictable adverse effects on protein coding genes and transcriptional regulatory regions. However, recent findings that DNA lesions (nuclear and telomeric) generate signaling responses that influence mitochondrial function ( Fakouri et al, 2018 ; Fang et al, 2016b ; Sahin et al, 2011 ), have identified a novel consequence of an overall effect of stochastic genomic damage on cell function and aging, thus connecting genome instability to mitochondrial dysfunction, two hallmarks of aging ( Lopez-Otin et al, 2013 ; Mattson and Arumugam, 2018 ).…”
Section: From Nuclear Dna Damage Response To Mitochondria Dysfunctionmentioning
confidence: 99%